Comparative Studies of Renal Function Indices in Hypertensive Diabetic and Normotensive Diabetic Subjects. - Olafusi, Oluwatosin (American Journal of Biomedicine and Pharmacy, 2024)
Diabetes mellitus and hypertension are interrelated diseases. The purpose of this study was to compare the renal function indices of hypertensive diabetic and normotensive diabetic subjects. This study was conducted in Osogbo local government in the capital city of Osun state, Nigeria. 40 hypertensive diabetic subjects, 40 normotensive diabetic subjects and 40 healthy subjects were selected for this study. The mean systolic blood pressure of hypertensive diabetic subjects (149.68 ± 7.54 mmHg) was significantly higher when compared to that of normotensive diabetic subjects (p<0.01). Also, the diastolic blood pressure of hypertensive diabetics (88.23 ± 4.13 mmHg) was significantly higher than normtensive diabetics (p<0.01). There was an increase in the mean BMI of hypertensive diabetic subjects (26.11 ± 4.06) when compared to that of the control subjects (P<0.05). The mean concentrations of potassium, bicarbonate, urea and uric acid (5.29±1.04,23.53 ±2.89,6.79 ±3.14 and 0.40 ± 0.17 mmol/l) respectively were significantly high (P<0.01) in hypertensive diabetic when compared to healthy subjects. Also, there were significant differences in the mean concentrations of potassium, bicarbonate, urea and uric acid (5.26±1.13, 24.45±2.90,6.80 ±2.54 and 0.42 ±0.17 mmol/1) respectively of normotensive diabetics when compared to control subjects. However, mean concentration of potassium, sodium, bicarbonate, urea and uric acid were statistically unchanged in hypertensive diabetic subjects when compared to normotensive diabetic subjects. There was inverse correlation between bicarbonate and systolic blood pressure (r= -0.22), bicarbonate and creatinine (r=-0.34), bicarbonate and chloride (r= -0.50). There was positive correlation between systolic and diastolic blood pressures (r=0.79), urea and creatinine (r= 0.50), urea and uric acid (r= 0.75), creatinine and uric acid (r= 0.42).Although, there were no significant differences in the renal function indices of hypertensive diabetic subjects when compared to normotensive diabetic subjects, these findings suggest that there were alterations in the renal function indices of both hypertensive diabetics and normotensive diabetics.